P049 HLA B27 transgenic rat: a new animal model of ileitis post-surgery reproducing inflammatory bowel disease. (16th January 2018) - Chau, A; Schneider, L; Chater, C; Speca, S; Djouina, M; Dubuquoy, C; Dubuquoy, L; Neut, C; Koriche, D; Pruvot, F R; Desreumaux, P; Zerbib, P; et al.
Abstract: Background: Ileal recurrence (IR) of Crohn's disease (CD) after ileocaecal resection (ICR) concerns the majority of the patients. Mechanisms and predictive factors of recurrence remain unclear. The aim of this study was to develop a reproducible animal model of IR of postoperative CD in HLA B27 rats. Methods: One hundred and fifteen rats were enrolled including (55 transgenic HLAB27 (Tg) rats and 60 non-transgenic wild-type (nTg) rats. We first evaluated IR and associated factors in 72 rats; at 12 weeks, 29 rats (14 Tg, 15 nTg) underwent ICR with ileo-colonic anastomosis compared with 19 rats (8 Tg, 11 nTg) who underwent a section-anastomosis of the small intestine (SAS) and 24 rats (12 Tg, 12 nTg) an open surgery without intestinal resection (OS). Impact of anastomosis type was then evaluated in 43 rats: 27 rats were operated by end-to-end anastomosis (EEA) (14 nTg, 13 Tg), and 16 rats by side-to-side anastomosis (SSA) (8 nTg, 8 Tg). Rats were monitored daily clinically and were sacrificed six weeks after surgery (18 weeks). At the sacrifice in rats with ICR, IR was double-blind assessed macroscopically by a small intestine score (SIS) (score 0–4) by two independent investigators. Histological analysis (score 0 to 6) and mucosal cytokine production assessed by qPCR were also performed. Results: After ICR a macroscopic IR was observed in 100% Tg rats compared with 0% nTg rats ( p < 0.0001). This recurrence was characterised by hyperemia of the ileal mucosa in 100% and by ulcerations in 80% of Tg animals. SIS was >3 in all Tg rats with ICR. No significant ileal lesion was observed in Tg and nTg rats who underwent SAS ( n = 19) and OS (n = 24) with SIS <2 ( p <0.05).In rats with ICR, histological score was significantly higher in Tg rats (score 4 to 6) compared with nTg rats (score 1 to 2, p < 0.05). Messenger RNAs expressions of TNF, IL17, IL1β above anastomotic ileum were also significantly higher in Tg rats ( p < 0.05). Concerning the anastomosis type, nTg rats did not show any digestive lesion. Tg rats with EEA had more severe lesions compared with Tg rats with SSA ( p = 0.0238) with 70% of EEA Tg rats with an SIS ≥ 2 compared with 25% of the SSA Tg rats. Conclusions: We report a reproducible model of post-operative recurrence after ICR in genetically predisposed HLA B27 rats.100% of HLA b27 rats exposed macroscopic, histologic and molecular recurrence in the terminal ileum 6 weeks after surgery. Type of the anastomosis impacted on the severity of ileal lesions with more severe lesions after EEA compare to SSA, suggesting the role of colonic reflux. This new animal model shares strong physiopathologic similarities with postoperative recurrence in CD patient and provide opportunities to better understand mechanisms involved in CD and to develop new therapeutic strategies.